2022
DOI: 10.1007/s00455-022-10459-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasonography in Neurogenic Dysphagia: A Systematic Review

Abstract: Swallowing disorders are common in neurological diseases, with dysphagia representing one of the most prevalent complications that may cause poor quality of life, reduce independence, and increase mortality. Rapid identification of dysphagia is necessary to reduce the risk of penetration and aspiration, and to early start rehabilitation protocols. Among the methods that can be used to evaluate dysphagia and its components, ultrasound imaging has been suggested to support the evaluation of dysphagia by providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Even though there are plenty of tools for evaluating muscle mass in the clinical setting, these are often expensive and not practical, and for these reasons, they are scarcely used preoperatively [ 4 ]. Muscle ultrasound (US) has been suggested to be feasible in clinical practice, providing quantitative measures of muscle architecture in sports medicine, geriatrics, and other medical disciplines [ 5 , 6 , 7 , 8 , 9 ]. In 2003, Narici et al reported that the loss of muscle mass associated with sarcopenia entails not only a decrease in muscle cross-sectional area and volume but also alterations in the spatial arrangement of muscle fibers within the muscle [specifically, fiber fascicle length (Lf), pennation angle (θ), and muscle thickness (Tm)], known as “muscle architecture” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are plenty of tools for evaluating muscle mass in the clinical setting, these are often expensive and not practical, and for these reasons, they are scarcely used preoperatively [ 4 ]. Muscle ultrasound (US) has been suggested to be feasible in clinical practice, providing quantitative measures of muscle architecture in sports medicine, geriatrics, and other medical disciplines [ 5 , 6 , 7 , 8 , 9 ]. In 2003, Narici et al reported that the loss of muscle mass associated with sarcopenia entails not only a decrease in muscle cross-sectional area and volume but also alterations in the spatial arrangement of muscle fibers within the muscle [specifically, fiber fascicle length (Lf), pennation angle (θ), and muscle thickness (Tm)], known as “muscle architecture” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dysphagia related to neurological disorders, there are other causes that occur due to different conditions, known as mechanical dysphagia, in which the anatomical structures responsible for swallowing suffer some structural damage, as occurs in head and neck cancers, cardiovascular diseases, lung diseases, and respiratory diseases 5 . When difficulty in swallowing is associated with respiratory diseases, there is a possibility of bronchoaspiration 6 , in which entry of food or fluids into the lower airways can generate pneumonia and death 7 .…”
Section: Introductionmentioning
confidence: 99%
“…When difficulty in swallowing is associated with respiratory diseases, there is a possibility of bronchoaspiration 6 , in which entry of food or fluids into the lower airways can generate pneumonia and death 7 . It is also known that the elderly are more susceptible to dysphagia due to the diseases, such as stroke and cardiovascular diseases, which accompany this condition 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%